Laughing with Sam Sly: The cultural politics of satire and colonial British identity in the Cape Colony, c. 1840-1850 - Holdridge, Christopher (Kronos: Southern African Histories, 2017)
This article examines Sam Sly's African Journal ( 1843-51 ), a literary and satirical newspaper published by William Layton Sammons in Cape Town. It contends that the newspaper utilised satire to forge British cultural affinity in the colony, as well as to encourage and preserve the conservative social boundaries of propriety and family values espoused by white middle-class colonists. This differed from the more widely studied position of satire as a subversive challenge to the established order, with Sammons avoiding sexually explicit, scandalous humour or overt attacks on personal character. In a period of growing white consensus, the African Journal's use of satire in the 1840s formed part of the cultural politics of establishing bourgeois values through the medium of appreciation of British literature and popular culture. Satire in Sam Sly's African Journal thus functioned ideologically to extend British cultural dominance and affinities, and to preserve and instil white bourgeois moral codes. Although much satire was shorn of the racial reality of the Cape Colony, seeking to replicate an impression of metropolitan whiteness, those satires that focused on race derided the Khoikhoi and Xhosa as incapable of achieving equality with whites, drawing on growing anti-humanitarian sentiment in the Cape. The African Journal's popularity, however, diminished in the face of the anti-convict agitation of 1848-50, when colonists opposed the landing of ticket-of-leave convicts from Ireland as an impediment to the goal of representative government, through petitions and boycotting supplying to the government. Satirising these measures as a radical betrayal of British loyalty, Sammons's support dwindled owing to his criticism of popular feeling.